The Caillaux Drama - Raphael, John N. (John Nathan), 1868-1917 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Caillaux Drama" by John N. Raphael is a historical account written in the early 20th century. The book centers around the notorious case of Madame Joseph Caillaux, who shot and killed Gaston Calmette, the managing editor of the newspaper "Figaro", in an act fueled by the paper's damaging campaign against her husband, the Minister of Finance. This incident reverberated through Parisian society, sparking intense public and political discourse. The opening of the book sets the stage for the unfolding drama by detailing the shocking events of March 16, 1914, when news broke that Madame Caillaux had shot Calmette in his office. It portrays the immediate chaos and disbelief that gripped Paris after the murder, as crowds surged around the "Figaro" building to learn more. Through a detailed narrative, the reader is introduced to not only the key players involved, notably Madame Caillaux and her husband, Joseph Caillaux, but also the societal and political implications of this high-profile murder, revealing the tensions that simmered beneath France$1 (Bs complicated political landscape. (This is an automatically generated summary.)s
Release date is 2016-07-30
E-text prepared by Clarity, Paul Marshall, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (https://archive.org/details/americana)
Keywords: Caillaux, Joseph, 1863-1944; Caillaux, Henriette; Calmette, Gaston, 1858-1914